The type species of the genus Blagorrhina Hippa, Mattsson & Vilkamaa (Diptera: Lygistorrhinidae) - Hippa, Heikki; Mattsson, Ingegerd; Vilkamaa, Pekka (Zootaxa, 2005)
When preparing the final copy of our paper on Lygistorrhinidae (Hippa et al. 2005), the type speciesdesignation for the genus Blagorrhina was lost. We here designate Blagorrhina blagoderovi Hippa,Mattsson & Vilkamaa as the type species of Blagorrhina Hippa, Mattsson & Vilkamaa.We thank Dr. Christian Thompson (Washington, D.C.) for pointing out the missing type species designation.